Chronic loading increases the number of leptin receptors in the human triceps brachialis: a study on professional tennis players - Olmedillas, H.; Fuentes, T.; Guadalupe-Grau, A.; Ponce-Gonzalez, J. G.; Santana, A.; Sanchis, J.; Calbet, J. A. L.; Guerra, B. (Archivos de medicina del deporte, 2008)
Leptin plays a crucial role in the regulation of appetite, body fat mass and basal metabolic rate. We have recently shown the presence of OB-R long and short protein isoforms (OB-R170, OB-R128 and OB-R98) in human skeletal muscle. Human obesity is characterised by a high concentration of leptin in plasma associated with leptin resistance. Leptin may also down-regulate leptin signalling in muscle by inducing the protein suppressor of cytokine signalling 3 (SOCS3). Recent evidence suggest that exercise restored the ability of leptin to increase the muscular fatty acid oxidation in obese rats without any change in the SOCS3 mRNA. However, there is no data about the effects of exercise on muscle leptin sensitivity in humans. Tennis is an excellent model to study muscle plasticity, since tennis players submit their dominant-arm to a huge amount of physical activity compared to their contralateral arm. Methods: Nine professional tennis players (24±2 years, 185±8 cm, and 78±10 Kg of body mass) underwent a body composition examination with a dual-x ray absorptiometer and three muscle biopsies one from the vastus lateralis and one from each triceps brachialis (short head). The muscle samples were processed for assessment of the leptin receptor protein isoforms, and SOCS3 protein expression by Western Blot. Results: The dominant arm had 14.2% higher muscle mass (P<0.05) and 62% greater OB-R170 protein expression (P<0.05) than the contralateral arm. Adipose tissue contamination in the triceps muscle biopsies can not explain the observed difference in OB-R170 amount between arms, as the perilipin A protein content was similar in both arms (P=0.4).Moreover, the amount of SOCS3 was similar in both arms (P=0.52). In the dominant arm there was an inverse correlation between OB_R170 protein expression and SOCS3 protein content (r=-0.67, P<0.05). However in the non-dominant arm there was no correlation between these variables (r=0.29, P=0.5). Conclusions: Skeletal muscle leptin receptors are up-regulated in the triceps brachialis in response to chronic loading. The latter combined with the fact that SOCS3 protein expression was not increased indicates that chronic loading may result in increased leptin sensitivity in human skeletal muscle